THE ROLE OF RENEWABLE ENERGY IN THE DEVELOPMENT OF THE "GREEN ECONOMY" (American Journal of Pedagogical and Educational Research, 2023)
This article provides information about the essence of the renewable energy source and the work carried out in Uzbekistan.